2017
DOI: 10.1016/j.chom.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota, Food Science, and Human Nutrition: A Timely Marriage

Abstract: Analytic advances are enabling more precise definitions of the molecular composition of key food staples incorporated into contemporary diets and how the nutrient landscapes of these staples vary as a function of cultivar and food processing methods. This knowledge, combined with insights about the interrelationship between consumer microbiota configurations and biotransformation of food ingredients, should have a number of effects on agriculture, food production and strategies for improving the nutritional va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 53 publications
0
55
0
Order By: Relevance
“…The relationship between the gut microbiota and feed efficiency has been demonstrated in several livestock animal species such as cattle (Guan et al, 2008), sheep (Perea et al, 2017) and pigs (Yang et al, 2017), thus suggesting this may be a generalized phenomenon across the whole animal kingdom. This thought is not unfounded, and decades of research on the human gut microbiota have also demonstrated a strong and dynamic interrelationship between dietary components, the gut microbiota and host's physiology (Barratt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the gut microbiota and feed efficiency has been demonstrated in several livestock animal species such as cattle (Guan et al, 2008), sheep (Perea et al, 2017) and pigs (Yang et al, 2017), thus suggesting this may be a generalized phenomenon across the whole animal kingdom. This thought is not unfounded, and decades of research on the human gut microbiota have also demonstrated a strong and dynamic interrelationship between dietary components, the gut microbiota and host's physiology (Barratt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Diet is an in uencer of the composition and function of the microbiota [29]. Adults with rheumatoid arthritis may be improved by vegan or Mediterranean diet [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…During the past two decades, the human microbiome has emerged as a biological system with the potential to significantly influence health and disease (Shreiner et al, 2015). Despite our limited understanding regarding its intricate relationship with the host and its environment (Foster et al, 2017), recent discoveries related to the human microbiome have opened new horizons in food science (Barratt et al, 2017), precision medicine (Wishart, 2016), and biotechnology (Taroncher-Oldenburg et al, 2018) among other fields. In parallel, advances in genomics and bioinformatics have provided inexpensive tools to acquire biological and clinical data, as well as the tools to translate the data into knowledge (Shoaie et al, 2015;Zeevi et al, 2015;Thaiss et al, 2016a;Korem et al, 2017;Baldini et al, 2018;Bauer and Thiele, 2018;Gilbert et al, 2018;Greenhalgh et al, 2018;Knight et al, 2018).…”
Section: Introductionmentioning
confidence: 99%